OPTIMIZING MAINTENANCE FREQUENCY ON INSTRUMENTATION WITH THE RELIABILITY CENTERED MAINTENANCE METHOD AT PT X - Mochammad Resha; Eko Wahyu Saputra; Chandra Salim (RADJA PUBLIKA, 2025)
In facing maintenance challenges in offshore oil and gas operational platforms, determining instrumentation components based on Safety and Environment Critical Element (SECE) with the Reliability Centered Maintenance (RCM) method requires component repair data in the 2019-2023 time interval. So far, maintenance intervals have been carried out conventionally without considering historical reliability data, which has led to over-maintenance and under-maintenance. This study aims to optimize the maintenance frequency of SECE instrumentation with the RCM approach to improve technical, operational, and economic efficiency, as well as ensure compliance with safety and environmental standards. The methodology used includes data collection, technical document analysis, reliability calculations, and the development and re-implementation of maintenance work in the system. The calculation results show that several instruments have a high level of reliability, such as the pressure transmitter at 99.86%, while the shutdown valve recorded the lowest reliability of 97.86%, which based on a significance test can be extended to a 12-month maintenance interval. Optimizing the maintenance interval resulted in a significant reduction in man-hour requirements, up to 27% on the entire platform while maintaining system reliability. Technical recommendations were also proposed, including the use of statistical approaches such as the Weibull distribution for further analysis. This research shows that a data-driven RCM approach not only improves system reliability but also resource efficiency and overall occupational safety.